2022
DOI: 10.1007/s00253-022-12037-3
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring fructooligosaccharides composition with engineered Zymomonas mobilis ZM4

Abstract: Zymomonas mobilis ZM4 is an attractive host for the development of microbial cell factories to synthesize high-value compounds, including prebiotics. In this study, a straightforward process to produce fructooligosaccharides (FOS) from sucrose was established. To control the relative FOS composition, recombinant Z. mobilis strains secreting a native levansucrase (encoded by sacB) or a mutated β-fructofuranosidase (Ffase-Leu196) from Schwanniomyces occidentalis were constructed. Both strains were able to produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
2
0
2
Order By: Relevance
“…The broad host range vector pBBR1MCS2 (Kovach et al., 1995 ) is frequently utilized in Z. mobilis (Braga et al., 2022 ; Herrera et al., 2021 ; Liu et al., 2020 ). pGB‐MPI‐068 carries the rep , oriV and mob elements of pBBR1MCS2 and was further modified to create acceptors fitting the Zymo‐Parts system.…”
Section: Resultsmentioning
confidence: 99%
“…The broad host range vector pBBR1MCS2 (Kovach et al., 1995 ) is frequently utilized in Z. mobilis (Braga et al., 2022 ; Herrera et al., 2021 ; Liu et al., 2020 ). pGB‐MPI‐068 carries the rep , oriV and mob elements of pBBR1MCS2 and was further modified to create acceptors fitting the Zymo‐Parts system.…”
Section: Resultsmentioning
confidence: 99%
“…The gene 0917 encodes β-fructofuranosidase [EC 3.2.1.26], and the gene 1378 encodes levansucrase [EC 2.4.1.10]. These two genes are important in sucrose catabolism ( Braga et al, 2022 ), and their downstream genes are either downregulated or of very low abundance. These results indicated that the transcription of 0917 and 1378 genes was significantly downregulated due to the decreased activity of catabolic sucrose in CR5301, caused by the addition of RC.…”
Section: Resultsmentioning
confidence: 99%
“…Both strains could produce a mix of FOS with a high concentration of 6-kestose. However, Z. mobilis ZM4_pB1-sacB produced 73.4 ± 1.6 g/L of FOS [184].…”
Section: From Genetic Engineering To Synthetic Biology To Produce Fru...mentioning
confidence: 94%